Implementasi Putusan Mahkamah Konstitusi melalui Permenaker Nomor 7 Tahun 2026 dalam Perlindungan Hak Konstitusional Pekerja Alih Daya - Yohanes Brilian Jemadur (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The regulation of outsourced work is not merely a matter of industrial relations, but also concerns the protection of workers’ constitutional rights. Constitutional Court Decision Number 168/PUU-XXI/2023 provides a constitutional direction for limiting outsourced work. As a follow-up, the government issued Minister of Manpower Regulation Number 7 of 2026 concerning Outsourced Work. This article analyzes the implementation of the Constitutional Court decision through the regulation in protecting the constitutional rights of outsourced workers. This research uses normative legal method. The study finds that the regulation strengthens worker protection, but still leaves issues of interpretation and supervision effectiveness.